Nanoparticle-mediated gene delivery techniques in plant systems - Shivashakarappa, Kuber; Marriboina, Sureshbabu; Dumenyo, Korsi; Taheri, Ali; Yadegari, Zeinab (Frontiers in Nanotechnology, 2025)
Plant genetic engineering is an evolving discipline that contributes to crop improvement by introducing desirable traits into crop plants, such as improved yield, enhanced nutrition value, and resistance to biotic and abiotic stresses. Plant transformation is carried out in two steps: Gene delivery into the plant cell and regeneration of the plant cell into the fertile plant. Gene delivery is an essential step in plant genetic transformation, and it is largely plant species-specific. Based on the mode of delivery the conventional plant gene delivery methods are divided into three main categories: biological (Agrobacterium-mediated transformation), physical (biolistic and electroporation), and chemical (Polyethylene glycol mediated and liposome-mediated gene delivery). Apart from species constraints, these methods have unique advantages and limitations, including random gene integration, low gene transfer efficiency, tissue damage, united gene alterations, time-consuming and labor-intensive plant regeneration protocols. Recent advancements in nanotechnology have introduced novel gene-delivery systems, utilizing micro and nanoparticles, which can overcome many limitations of conventional plant gene delivery methods by exhibiting superior transformation efficiency, demonstrate compatibility with biological systems, offer protection to different cargoes, and hold significant capability for enhancing plant regeneration. Nanoparticles are well recognized for its flexible size, shape, and cargo-binding properties, which enable them to surpass defensive primary cell wall barrier and it can be a promising candidate for plant gene delivery applications. However, delivering the nanoparticles and cargo complexes into plants is a critical step of the gene delivery process, and have not been thoroughly explored. In this review, we provide comprehensive insights into nano-delivery systems and detailed methods of introducing nanoparticle complexes into plant tissues. Further, we also discuss techniques such as syringe infiltration, vacuum infiltration, biolistic methods, magnetofection, ultrasound-mediated delivery, passive diffusion, cellular uptake, and spray method. This review serves as a valuable resource for advancing plant gene transformation using nanoparticles, offering guidance on the most effective delivery methods to enhance plant genetic engineering outcomes.